2019
DOI: 10.1128/jvi.00122-19
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Anion Channel Protein 2 (VDAC2) and Receptor of Activated Protein C Kinase 1 (RACK1) Act as Functional Receptors for Lymphocystis Disease Virus Infection

Abstract: In previous research, a 27.8-kDa protein in flounder Paralichthys olivaceus gill (FG) cells was identified as a putative cellular receptor (27.8R), which mediated lymphocystis disease virus (LCDV) infection via interaction with a 32-kDa viral attachment protein (VAP) of LCDV, and monoclonal antibodies (MAbs) against 27.8R and 32-kDa VAP were developed. In this study, the 27.8R was identified as voltagedependent anion channel protein 2 (VDAC2) and receptor of activated protein C kinase 1 (RACK1) of flounder. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…In LCDV infection, we previously observed that the LCDV 32 kDa VAP interacts with VDAC2 and RACK1 receptors to initiate virus infection. VDAC2/RACK1 knockdown through siRNA significantly reduced LCDV copy numbers, whereas VDAC2/RACK1 expression on LCDV-nonpermissive EPC conferred susceptibility to LCDV infection [ 15 ]. The LCDV 32 kDa VAP is encoded by the ORF038 gene of LCDV isolated in China (LCDV-C) [ 14 , 50 ], and the LCDV-C ORF038 gene had homologues with genes encoding SGIV VP19 and rana grylio virus envelope protein 2L [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In LCDV infection, we previously observed that the LCDV 32 kDa VAP interacts with VDAC2 and RACK1 receptors to initiate virus infection. VDAC2/RACK1 knockdown through siRNA significantly reduced LCDV copy numbers, whereas VDAC2/RACK1 expression on LCDV-nonpermissive EPC conferred susceptibility to LCDV infection [ 15 ]. The LCDV 32 kDa VAP is encoded by the ORF038 gene of LCDV isolated in China (LCDV-C) [ 14 , 50 ], and the LCDV-C ORF038 gene had homologues with genes encoding SGIV VP19 and rana grylio virus envelope protein 2L [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For viruses that enter via caveolae-mediated endocytosis, receptor proteins are usually abundant in the caveolae of susceptible cells [ 67 ]. VDAC2 and RACK1 are widely distributed in caveolae [ 16 , 17 , 18 , 19 , 20 , 21 ], and VDAC2 and RACK1 knockdown or blocking inhibits LCDV infection of FG cells [ 15 ]. To elucidate the roles of VDAC2 and RACK1 in LCDV entry, we confirmed that LCDV could co-localize with VDAC2 and RACK1, and CTB also co-localized with VDAC2 and RACK1, while LCDV partially co-localized with CTB, indicating that VDAC2 and RACK1 mediate LCDV infection, and CTB might co-localize with VDAC2 and RACK1 during LCDV entry, even though the receptor protein for CTB in caveolae is ganglioside [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations